2016
DOI: 10.2217/bmm-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

FLNA is a Predictor of Chemoresistance and Poor Survival in Cervical Cancer

Abstract: Aim: To investigate the expression of FLNA and its potential prognostic significance in cervical cancer. Patients & methods: Real-time PCR was performed to evaluate the expression levels of FLNA in 44 pairs of cervical cancer and matched normal adjacent tissues. Kaplan–Meier analysis and Cox proportional hazards model were used to examine the correlation between FLNA expression levels and overall survival in cervical cancer patients. Results & conclusion: FLNA was significantly upregulated in cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…FLNA, coding for filamin A, a non-muscle actin filament cross-linking protein, is a downstream target of the nuclear transcription factor Sp1 [52], which is also regulated by ERK1/2 [53]. Reduced FLNA levels were observed in PEA-15AA-transfected cells in this study, and also correlated with increased cisplatin sensitivity in a mouse xenograft model [54] and with improved overall survival in patients [55] according to previous reports. Filamin a was also found to promote cancer growth [56] and to play an important role in repair of DNA damage [57].…”
Section: Discussionsupporting
confidence: 86%
“…FLNA, coding for filamin A, a non-muscle actin filament cross-linking protein, is a downstream target of the nuclear transcription factor Sp1 [52], which is also regulated by ERK1/2 [53]. Reduced FLNA levels were observed in PEA-15AA-transfected cells in this study, and also correlated with increased cisplatin sensitivity in a mouse xenograft model [54] and with improved overall survival in patients [55] according to previous reports. Filamin a was also found to promote cancer growth [56] and to play an important role in repair of DNA damage [57].…”
Section: Discussionsupporting
confidence: 86%
“…Hence, high-risk predictors must be identified to enable stratified management. Filamin A (FLNa) can be used as a predictor of chemotherapy sensitivity and as a biomarker of prognosis ( 11 ), and uncoupling protein 2 (UCP2) can be used as an indicator of chemotherapy sensitivity in patients with advanced CC ( 12 ). The present study focused on FLNa and UCP2 and investigated their expression levels in CC, their roles in the development and progression of CC, and their value for early diagnosis and prognosis prediction of CC.…”
Section: Introductionmentioning
confidence: 99%
“…Down regulation of the gene has been observed in a wide range of human malignant tumors, including gastric and renal cancer. However, some studies have reported that FLNA was significantly up-regulated in cervical cancer and has a good predictive effect, which can be used as a prognostic signature of cervical cancer (22). VCL encodes focal adhesion protein, participates in the formation of cytoskeleton and focal adhesion, and the gene also connects cells with extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%